2012
DOI: 10.1007/s11427-012-4345-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility of algal symbionts to photo-inhibition resulting from the perturbation of coral gastrodermal membrane trafficking

Abstract: The stability of cnidarian-dinoflagellate endosymbioses is dependent upon communication between the host gastrodermal cell and the symbionts housed within it. Although the molecular mechanisms remain to be elucidated, existing evidence suggests that the establishment of these endosymbioses may involve the sorting of membrane proteins. The present study examined the role of host gastrodermal membranes in regulating symbiont (genus Symbiodinium) photosynthesis in the stony coral Euphyllia glabrescens. In compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Lesser, 1996;Jantzen et al, 1998;Blackstone, 2001;Franklin et al, 2004;Chen et al, 2012). This probe requires incubation, typically for 1 h in the dark.…”
Section: Measures Of Ros Rns and Nad(p)h In Host Stolonsmentioning
confidence: 99%
“…Lesser, 1996;Jantzen et al, 1998;Blackstone, 2001;Franklin et al, 2004;Chen et al, 2012). This probe requires incubation, typically for 1 h in the dark.…”
Section: Measures Of Ros Rns and Nad(p)h In Host Stolonsmentioning
confidence: 99%
“…Zooxanthellates DNA was extracted from the coral fragments, and the clades were successively identified according to the internal transcribed spacer rDNA sequence [21]. After the pre–treatment procedure, selected clones were sequenced and the obtained sequences were searched for and aligned in the NCBI GenBank Database with BLAST (http://www.ncbi.nlm.nih.gov/).…”
Section: Methodsmentioning
confidence: 99%
“…During the initial step of the endosymbiotic process, SGCs are involved in the recognition and phagocytosis of Symbiodinium 16, 17 . Proteomic analyses have demonstrated that SGC plasma membrane proteins are involved in the molecular chaperone/stress response, cytoskeletal remodeling, and energy metabolism 18 .…”
Section: Introductionmentioning
confidence: 99%